Legality of Refusal to Provide BPJS Patients Health Facilities Based on Fatwa of The Indonesian Ulema Council (MUI) - Muhammad Azis Satria; Iwan Iwan; Sajjad Hussain (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This research delves into the legal consequences and Sharia compliance aspects of rejecting BPJS Kesehatan (Healthcare and Social Security Agency) patients in Medan City. Employing an empirical research methodology with interviews and a conceptual approach, the study explores rejection factors such as incomplete administrative files and inadequate facilities. Guided by DSN-MUI Fatwa NO.98, the findings highlight that rejecting BPJS patients exposes health facilities to civil, administrative, and criminal sanctions. Despite efforts by the Indonesian Ulema Council (MUI) to guide Sharia compliance, challenges persist in the effective implementation of the fatwa by BPJS Health and affiliated facilities. Technical and systemic gaps hinder seamless alignment with Sharia principles. The study emphasizes the urgent need for policy adjustments to bridge the gap between legal requirements, Sharia compliance, and the efficient functioning of the healthcare system. Contributing to ongoing discussions, this research advocates for comprehensive solutions to ensure equitable healthcare access for all Indonesian citizens. By addressing the intricacies of BPJS Kesehatan patient rejections within the context of Sharia principles, the study provides valuable insights for policymakers, healthcare practitioners, and stakeholders striving for a more effective and inclusive healthcare system in Indonesia